The Aerodrome : A Love Story - Warner, Rex, 1905-1986; with an Introduction by Moorcock, Michael (London Vintage Books, 2007)
A model of efficiency and order, the aerodrome stands on the hill looking down on the village below. Roy, coming of age in the messy, violent and adulterous world of the villagers, is simultaneously attracted and repelled by this strange place and by the powerful figure of the Air Vice-Marshal. Soon he is led to leave his family, his friends and his love in order to join the aerodrome and confront the secrets of this mysterious and sinister place .
Keywords: Fascism -- Fascists -- English fiction